Exposures to common shocks along supply chains and relative performance evaluation in CEO compensation contracts - Wu, YiLin; Ieong, Richard Lok-Si; Thomas, Shawn (Journal of Corporate Finance, 2025)
A fundamental prediction from principal-agent theory is that firms facing greater ex ante exposures to exogenous common shocks should more frequently utilize relative performance evaluation (RPE) in CEO compensation contracts. Recent advances in modeling the economy as a supply network consisting of sectors connected through input-output linkages establish that industries positioned more centrally or upstream face greater ex ante exposures to exogenous common shocks propagating through the network. This paper investigates the impact of firms' network positions on the use of RPE in CEO compensation. We find that firms in industries positioned more centrally or upstream use RPE more frequently and base greater fractions of CEO pay on RPE. We also document that network positions explain variation in firms' RPE-plan implementation via the selection of peers. Our findings are consistent with boards using RPE to filter from CEO pay exogenous shocks to firm performance inherent in firms' supply network positions.